Confucian rituals and Chinese villagers ritual change and social transformation in a southeastern Chinese community, 1368-1949 - Liu, Yonghua, 1970- (Religion in Chinese societies, 2013)
In 'Confucian rituals and chinese villagers', Yonghua Liu presents a detailed study of how a southeastern Chinese community experienced and responded to the process whereby Confucian rituals - previously thought unfit for practice by commoners - were adopted in the Chinese countryside and became an integral part of village culture, from the mid fourteenth to mid twentieth centuries. The book examines the important but understudied ritual specialists, masters of rites (lisheng), and their ritual handbooks while showing their crucial role in the ritual life of Chinese villagers. This discussion of lisheng and their rituals deepens our understanding of the ritual aspect of popular Confucianism and sheds new light on social and cultural transformations in late imperial China.0.